Exploring the relationship between job demands, resource, and psychological well-being: A study in the hospitality and tourism industries - Marks, Joshua Blaine (University of the Witwatersrand, Johannesburg, 2024)
Identified as a key factor contributing to elevated levels of individual performance and thus organisational performance, ensuring ideal levels of individual psychological well-being has grown increasingly important within organisations, especially following the onset and recession of the COVID-19 pandemic. Despite the pandemic having receded, its initial impact left lasting effects on various industries, particularly the tourism and hospitality industries as these industries saw a drastic reduction in workforce size and revenue generated. This has prompted the implementation of nationwide recovery efforts; however, these have been found to be primarily aimed at addressing the financial and economic impacts of the pandemic with minimal consideration for addressing the psychological impacts of the pandemic. This study aimed at evaluating the current state of individual psychological well-being of individuals working in the tourism and hospitality industries in South Africa. Given the broad nature of the psychological well-being construct, attempts to evaluate it in the work context have proved difficult. Hence it is for this reason that this study evaluated psychological well-being with reference to the experience of work engagement and burnout, as these constructs have been conceptualised as indicators of psychological well-being. Therefore individual psychological well-being was assessed through the exploration of the potential relationships between various job characteristics and the experience of work engagement and burnout. The sample consisted of 65 participants from organisations within the tourism and hospitality industries in South Africa. Participants were required to complete a questionnaire that comprised of a demographic information section, the Job-Demands Resources Scale (JDRS), the Maslach Burnout Inventory-Health Services Survey (MBI-HSS), and the 9-item Utrecht Work Engagement Scale (UWES-9). The results generated indicated the presence of significant, weak to moderate relationships between the variables of interest, with few exceptions. Furthermore, the significant regression models generated by the analysis provided insight into the relative contributions of the chosen job characteristics to the experience of work engagement and burnout. The results were discussed within the broader literature on the concepts of job demands and job resources, and the experience of work engagement and burnout.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts by Coursework and Research Report in Organizational Psychology to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: Work engagement; Burnout; Job demands; Job resources; Psychological well-being; COVID-19 pandemic; UCTD; SDG-8: Decent work and economic growth